Analisis Perlindungan Hukum Terhadap Pekerja Harian Lepas Menurut Undang-Undang No. 13 Tahun 2003 Tentang Ketenagakerjaan - Muhammad Caesar Raflianto; Akbar Sayudi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Legal protection for casual daily workers is contained in Law Number 13 of 2003. Protection for workers includes social, economic and technical protection. However, casual daily workers do not yet receive full protection from a social, economic and technical perspective. Many workers' rights have not been fulfilled, such as wages, and there is no social security for workers, if workers experience work accidents or occupational health problems while carrying out their work.This research aims to determine the regulation of casual daily workers and legal protection for casual daily workers according to Law Number 13 of 2003 concerning Employment. This research is a type of normative legal research. The data used is secondary data consisting of primary, secondary and tertiary legal materials followed by document studies, regulations and related theories which produce descriptive-analytical data. The research results show that the regulation of casual daily workers is based on PKWTT which can be made in written or verbal form. Meanwhile, the PKWT provisions in Article 51 paragraph (2) of Law Number 13 of 2003 are required to be in writing, this aims to provide protection and certainty to workers/laborers. Legal protection for casual daily workers includes: protection of wages, protection of workers' health and safety, and protection of Social Security. It is hoped that relevant employers and governments will pay more attention to the rights of each worker so that they are adjusted to the mandate of Law Number 13 of 2003, because casual daily workers also work based on work agreements and have the same rights.